Relevance Feedback in Content Based Image Retrieval: A Review - Manesh B. Kokare; Pushpa B. Patil (Journal of Applied Computer Science & Mathematics, 2011)
This paper provides an overview of the technical achievements in the research area of relevance feedback (RF) in content-based image retrieval (CBIR). Relevance feedback is a powerful technique in CBIR systems, in order to improve the performance of CBIR effectively. It is an open research area to the researcher to reduce the semantic gap between low-level features and high level concepts. The paper covers the current state of art of the research in relevance feedback in CBIR, various relevance feedback techniques and issues in relevance feedback are discussed in detail.